2014
DOI: 10.1080/15374416.2014.904233
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Research on Psychotherapy for Adolescent Depression

Abstract: Research over the past 3 decades has shown that psychotherapy can successfully address adolescent depression. Cognitive behavioral models have been most extensively and rigorously tested, with evidence also supporting interpersonal psychotherapy and attachment-based family therapy. However, the vast majority of studies have focused on short-term treatment of depressive episodes, even as evidence accumulates that depression is frequently a recurring condition extending into adulthood. Moreover, treatment studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 102 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…As early intervention leads to better outcomes for adolescents at risk of recurrent episodes, and adolescents who respond well to treatment for depression still often experience later recurrence (Curry, 2014), emphasis should be placed on identifying those at risk for recurrent episodes using premorbid risk factors. Early pubertal timing, parental history of depression, child abuse, negative cognitive style, and high levels of negative emotionality and externalizing symptoms at an early age may be used to predict the likelihood of recurrent episodes during adolescence and so aid in the premorbid identification of individuals likely to have a chronic course of depression over the life span.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early intervention leads to better outcomes for adolescents at risk of recurrent episodes, and adolescents who respond well to treatment for depression still often experience later recurrence (Curry, 2014), emphasis should be placed on identifying those at risk for recurrent episodes using premorbid risk factors. Early pubertal timing, parental history of depression, child abuse, negative cognitive style, and high levels of negative emotionality and externalizing symptoms at an early age may be used to predict the likelihood of recurrent episodes during adolescence and so aid in the premorbid identification of individuals likely to have a chronic course of depression over the life span.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent depressive episodes during adolescence result in social, educational, and occupational impairment as well as increased risk for suicide, substance abuse, and other forms of psychopathology (Birmaher, Arbelaez, & Brent, 2002; Hammen, Brennan, Keenan‐Miller, & Herr, 2008; Wilson, Capuano, et al, 2014; Wilson, Vaidyanathan, Miller, McGue, & Iacono, 2014). Predicting and preventing the recurrence of depression remains an important clinical challenge (Curry, 2014; Lewinsohn, Allen, Seeley, & Gotlib, 1999; Lewinsohn, Rohde, Klein, & Seeley, 1999; Melvin et al, 2013), and there is a need to identify risk factors specifically associated with the recurrence of depression (Burcusa & Iacono, 2007; Lewinsohn, Allen, et al, 1999; Lewinsohn, Rohde, et al, 1999; Monroe & Harkness, 2005). However, relatively little is known about the risk factors that prospectively predict recurrent depressive episodes in youth.…”
Section: Introductionmentioning
confidence: 99%
“…As evidence-based forms of stress reduction for adolescents are often limited to cognitive-based therapy which may have limited efficacy over the long term (Curry, 2014) and active coping measures which have limited effectiveness on psychological functioning particularly with uncontrollable interpersonal stressors (Clarke, 2006), strengthening one’s ability to be self-compassionate may offer adolescents an additional personal resource which they can access when needed. The Mindful Self-Compassion program for adults, created and piloted by Neff and Germer (2013), has demonstrated that self-compassion can be developed and maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is one of the most critical challenges often associated with adolescent depression, and it remains the third leading cause of death among adolescents worldwide (WHO, ). Several studies have been conducted over recent decades to address adolescent depression and we learned that approaches like cognitive behavior therapy (CBT) and pharmacotherapy are among the most effective treatments (Brent et al., ; Curry, ; Garber et al., ; Hankin, ; TADS, ; Webb, Auerbach, & DeRubeis, ). However, the evidence for treatments of adolescent depression is less well established than for adult populations (Lewis et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinicians need to closely monitor adolescents during the first few weeks of antidepressant treatment. In addition, helping adolescents learn how to regulate cognitive processes and problem solve (e.g., through CBT) was found promising (Curry, ; Webb et al., ).…”
Section: Introductionmentioning
confidence: 99%